Community physical therapeutical rehabilitation of paraplegia; challenge for a Fallot Tetralogy (Original) (Revista científica Olimpia, 2020)
This article presents the research carried out to contribute to the solution of the problem that  exists in relation to the care of a patient suffering from Tetralogy of Fallot who has not yet  undergone surgery, which is aggravated by his paraplegic condition as a result of this cardiac  complication, with such notable consequences as lack of sensation in the lower extremities and  muscle weakness. There are few known physical activity related alternatives to rehabilitate this  type of patient. In view of this situation, the authors of the work have carried out research to  answer the following problem: How to contribute to the community therapeutic physical  rehabilitation of a paraplegic patient with Tetralogy of Fallot in the North Popular Council of the  municipality of Urbano Noris? To this end, the objective has been to draw up a community  therapeutic physical exercise program to contribute to the rehabilitation of a paraplegic patient  with Tetralogy of Fallot for his return to an active social life. The selected sample coincides with  the population; He is a young adult of 34 years of age of white race, resident in the North  Popular Council of the Urbano Noris municipality, Holguín province, Cuba, who lives with a  brother, orphaned by a mother who helped him in everything, so for these and other reasons his  self-validity should be stimulated. For all these reasons, the investigation is important and  pertinent.
Keywords: rehabilitation; community therapeutic physical exercises; paraplegia; tetralogy of fallot